Proposed Amendment of the Extended Fund Facility : Considerations to Extend the Duration of Extended Arrangements on Approval from Three to Four Years. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
The EFF Decision currently provides that extended arrangements will be approved for periods not exceeding three years but that, where appropriate, the period of an existing arrangement may be lengthened to a duration of up to four years. This note proposes that the EFF Decision be amended to allow for extended arrangements to be approved for up to four years from the outset. The reforms to the IMF lending toolkit since 2009 have injected additional flexibility and allowed better tailoring to countries' varying circumstances. These reforms have enabled the Fund to better respond to the wide-ranging needs of member countries by, among other things, establishing new and more tailored facilities, increasing access limits, clarifying exceptional access criteria, streamlining conditionality, and reforming charges while maintaining adequate Fund safeguards.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet